Basic principles of low-rise residential floating buildings design - Shekhorkina, Svitlana (Lviv Polytechnic Publishing House, 2015)
Floating building is a complex engineering structure, which combines functional features of typical homes and vessels. Currently there are many realized projects of buildings on the water, represented by different objects such as restaurants, hotels, cottage, etc. Following research aims to develop design procedure for low-rise residential floating buildings taking into account exploitation peculiarities. Results. The method of technical parameters of low-rise floating dwelling houses calculation, considering the demands of Ship register of Ukraine and current building codes have been proposed. Using 3D finite elements model of representative floating house, data about stress-strain state of floating building elements was obtained.
Keywords: low-rise floating houses; pontoons; stress-strain state; bearing capacity; structural-technological parameters; design